Mesopotamian eye disease texts: the Nineveh treatise - Geller, Markham J. (Die babylonisch-assyrische Medizin in Texten und Untersuchungen, 2020)
This volume is the first English edition of the Nineveh Series on eye disease from the royal library of Ashurbanipal, 7th century BCE. It is the longest surviving ancient work on opthalmology, anticipating by centuries the Hippocratic treatise on the eye. The Nineveh series represents a systematic array of eye symptoms and therapies, also showing commonalities with Egyptian and Greco-Roman medicine